Effect of intravitreal conbercept treatment before vitrectomy in proliferative diabetic retinopathy - Jian-Bo Mao; Han-Fei Wu; Yi-Qi Chen; Shi-Xin Zhao; Ji-Wei Tao; Yun Zhang; Bin Zheng; Lin Wang; Li-Jun Shen (International Journal of Ophthalmology, 2018)
AIM: To evaluate the safety and efficacy of intravitreal conbercept (IVC) injections as pretreatment for pars plana vitrectomy (PPV) in severe proliferative diabetic retinopathy (PDR). METHODS: This was a retrospective chart review of all patients who underwent PPV for PDR from January 2014 to October 2016. Patients who underwent IVC injection before PPV were assigned to the IVC group; the others were assigned to the control group. The IVC was performed 3-7d before surgery in the IVC group. All the eyes in the two groups were operated by the same doctor to complete the vitrectomy. Intraoperative complications and the changes in best-corrected visual acuity (BCVA) before and after surgery were compared between the two groups. RESULTS: A total of 68 eyes of 63 patients (22 eyes in the IVC group and 46 eyes in the control group) were examined. The risk of intraoperative bleeding was lower in the IVC group (2/22) than in the control group (25/46, P=0.000). Furthermore, the use of endodiathermy was significantly lower in the IVC group (1/22) than in the control group (12/46, P=0.047). The surgical time in the IVC group (112.64±34.52min) was significantly shorter than in the control group (132.85±40.04min, P<0.05). Compared to the BCVA before surgery, the mean BCVA was significantly improved after surgery for both groups (P<0.05). CONCLUSION: PPV is an effective treatment and can improve vision in patients with PDR. Preoperative intravitreal injection of conbercept could reduce the chances of intraoperative bleeding and the use of endodiathermy and shorten the operative time, which are beneficial in the management of PDR.